Implementasi Kurikulum Merdeka Belajar Pada Mata Pelajaran Akidah Akhlak di Madrasah Aliyah Negeri Binjai - Mona Febrica Silva; Sokon Saragih; Muhammad Basri (PT. Pustaka Cendekia Publisher, 2024)
Abstract. This study aims to understand the steps in implementing the Merdeka Learning Curriculum in the Akidah Akhlak subject at Madrasah Aliyah Negeri Binjai, including the factors that support and hinder its implementation, as well as the strategies teachers use to overcome these obstacles. The study employs a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The research subjects include the Head of the Madrasah, the Deputy Head of Curriculum, and the Akidah Akhlak teacher for class X-1. The findings indicate that the implementation of the Merdeka Learning Curriculum starts with planning and consists of three stages: introduction, core, and conclusion, although the P5 and PPRA projects have not been fully implemented. Evaluation is carried out through summative and formative assessments, as well as cognitive, affective, and psychomotor evaluations. Identified obstacles include a lack of training for educators and a mindset that has not fully adapted to the curriculum. Efforts to address these challenges include participating in workshops, enhancing teacher creativity, and sharing knowledge with fellow educators.